Analisis Peran Lembaga Pembiayaan Syariah dalam Pengembangan UMKM di Kota Jambi - Ilham Wahyudi; Enggar Diah Puspa Arum; Muhammad Ridwan (Jurnal Akuntansi & Keuangan Unja, 2018)
The purpose of this research is to analyze the key success factors of sharia financing systems to strengthening empower Small Medium Enterprises (SME) in Jambi. Study was developed by secondary data observation and deep interview regarding sharia financing. The result indicates that sharia financing was not a primary choice to support SME’s capital requirement. Furthermore inadequate understanding of sharia financing plays a dominant role in the selection of financing institution. Keywords : Financing sharia, Small Medium Enterprise.